2021
DOI: 10.1056/nejmoa2024277
|View full text |Cite
|
Sign up to set email alerts
|

Sotatercept for the Treatment of Pulmonary Arterial Hypertension

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
230
1
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 331 publications
(254 citation statements)
references
References 26 publications
9
230
1
14
Order By: Relevance
“…87 However, serious adverse events were common and included subdural hematoma in patients who were Sotatercept is a novel, first-in-class recombinant fusion protein that is undergoing evaluation in PAH. 89 Sotatercept binds activins and growth differentiation factors to restore homeostasis between pro-and anti-proliferative signals in the TGFβ superfamily pathway, which are imbalanced in PAH. In the PULSAR trial, treatment with sotatercept was associated with a significant reduction in PVR.…”
Section: Additional Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…87 However, serious adverse events were common and included subdural hematoma in patients who were Sotatercept is a novel, first-in-class recombinant fusion protein that is undergoing evaluation in PAH. 89 Sotatercept binds activins and growth differentiation factors to restore homeostasis between pro-and anti-proliferative signals in the TGFβ superfamily pathway, which are imbalanced in PAH. In the PULSAR trial, treatment with sotatercept was associated with a significant reduction in PVR.…”
Section: Additional Therapiesmentioning
confidence: 99%
“…Haematological adverse events were anticipated and noted, including thrombocytopaenia and polycythaemia. 89 Indeed sotatercept has previously been studied as a potential treatment of anaemia in patients with haematological malignancy. 90 The precise mechanism of thrombocytopaenia and associated clinical implications require exploration.…”
Section: Anticoagulation Antiplatelets and Novel Therapeutics In Pahmentioning
confidence: 99%
“…O primeiro estudo clínico nacional com medicamentos para HAP teve início em 2002, e a participação em ensaios clínicos multicêntricos internacionais se iniciou já em 2003. Desde então, praticamente o desenvolvimento de todos os novos fármacos contou com a participação de pesquisadores nacionais, não apenas com a inclusão de um número significativo de pacientes em estudos clínicos de grande relevância, (8,9) mas também no desenvolvimento de vários dos protocolos desses mesmos estudos. Portanto, nosso país contribuiu de forma objetiva para que hoje o mundo tenha 16 medicamentos aprovados para o tratamento da HAP.…”
Section: Editorialunclassified
“…This signaling pathway dysregulation plays a major role, and some studies have indeed demonstrated that it also controls progenitor and stem cell behavior. Thus recent results of a protector effect of a BMP treatment in Bmpr2 mutated mice [2] or of a proteic compound acting as a Transforming Growth Factor β (TGF-β) decay molecule designed to counterbalance the deficient BMP pathway [3] could also involve regulation of vascular progenitor and stem cells. Pulmonary hypertension is characterized by excessive pulmonary vascular occlusive remodeling with an increased medial thickness of normally muscularized arterioles and muscularization of previously non-muscularized arterioles.…”
Section: Introductionmentioning
confidence: 99%